Fiscal Sustainability : The Case of Eritrea - Yamauchi, Ayumu (Washington, D.C. : International Monetary Fund, 2004)
The paper examines fiscal sustainability issues for the case of Eritrea but has wider implications for addressing fiscal and debt sustainability. It begins with a formal definition and explanation of analytical sustainability indicators, followed by an assessment of the causes of fiscal deficits and their impact on the usual indicators of fiscal and external debt sustainability. The paper then goes beyond the usual analytical indicators by attempting to identify how and through which channels fiscal and other economic policies have affected the behavior of endogenous variables that in one way or another influence sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet